Essentials of athletic training - Arnheim, Daniel D.; Prentice, William E. (Boston, Mass. : WCB/McGraw-Hill, 1999)
"This book provides the reader with most current information possible on the subject of prevention and basic care of sports injuries. The general philosophy of the text is that adverse effects of physical activity arising from participation in sport should be prevented to the greatest extent possible. Overall, this text is designed to take the beginning student from general to more specific concepts. Each chapter focuses on promoting an understanding of the prevention and care of athletic injuries."
Includes glossary and index.
English text.
Keywords: Physical education and training